Assistance in Demographic Administration Innovation in Surabaya - I Dewa Gde Satrya (Research Collaboration Community (RCC), 2023)
Community service with students in the demographic administration internship program held by the Surabaya City Government’s Demographic and Civil Registration Office is carried out by means of students helping demographic administration tasks in 4 sub-districts within the Sambikerep District area. Namely, Made Village, Bringin Village, Sambikerep Village and Lontar Village. Through this activity, students benefit in terms of growing soft skills in terms of communication skills, adapting to the environment, working with others and time management. The benefits for the kelurahan are getting help from students and enthusiasm in providing services with the involvement of students.